2018
DOI: 10.1002/eco.1959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of discharge and habitat type on the occurrence and severity of Didymosphenia geminata mats in the Restigouche River, eastern Canada

Abstract: Since 2006, the Restigouche River watershed, eastern Canada, has been affected by nuisance growths of the mat‐forming diatom, Didymosphenia geminata. In 2010, in view of the potential impacts of this alga on the local Atlantic salmon fishery, we created a volunteer monitoring network to assess D. geminata mat severity within the watershed. Over the course of 6 monitoring summers, more than 1,200 observations of D. geminata mat severity were reported in 20 subwatersheds of the Restigouche River basin. Observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Our results indicate that the environmental parameters analyzed in this investigation showed little variability in the study period, in contrast to the great variability observed in D. geminata coverage. Thus, based on these results and in accordance with [17], the spatial variability in the coverage of D. geminata mats is explained by the habitat characteristics, and it is necessary to acquire data for long time series (annual, inter-annual) to highlight the importance of the environmental and hydrological variables that drive these changes. In our study, we emphasize that the application of the multivariate linear model indicated that conductivity, temperature and total phosphorus concentration were highly correlated with coverage of this microalga.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our results indicate that the environmental parameters analyzed in this investigation showed little variability in the study period, in contrast to the great variability observed in D. geminata coverage. Thus, based on these results and in accordance with [17], the spatial variability in the coverage of D. geminata mats is explained by the habitat characteristics, and it is necessary to acquire data for long time series (annual, inter-annual) to highlight the importance of the environmental and hydrological variables that drive these changes. In our study, we emphasize that the application of the multivariate linear model indicated that conductivity, temperature and total phosphorus concentration were highly correlated with coverage of this microalga.…”
Section: Discussionmentioning
confidence: 63%
“…Observations have shown that D. geminata has a high tolerance to changes in water quality [11][12][13] and its massive proliferation is mainly associated with low phosphorus concentrations [6,[14][15][16], low current velocity and depth [17][18][19]. In addition, its ability to completely cover various riverbed substrates, make this benthic diatom not only a threat to other aquatic organisms, but also one of the most damaging invasive species in river ecosystems [7,16,20,21], as it alters the availability of habitat for benthic species, causing changes in the food chain [2,22].…”
Section: Introductionmentioning
confidence: 99%
“…2 suggested it was increased concentrations of organic, rather than dissolved reactive phosphate, resulting from climate change which were responsible. Later on, parameters other than phosphorous (but that also can be affected by climate change), such as pH, hydrology (discharge and water movement) and irradiation, also have been suggested as possible bloom triggers, based on statistical correlations 6,1315 .…”
Section: Introductionmentioning
confidence: 99%
“…D. geminata has expanded rapidly outside its native distribution range in the last decade ( [69], successfully invading rivers and lakes of New Zealand, Argentina and southern Chile. [25,61,62]. The invaded systems have transparent and cold water with reduced nutrient concentrations; they have low levels of anthropogenic intervention and great recreational importance [6,8,36].…”
Section: Introductionmentioning
confidence: 99%